1984
DOI: 10.1007/bf00222480
|View full text |Cite
|
Sign up to set email alerts
|

Biotin analogs activate guanylate cyclase

Abstract: The sulfur atom in the vitamin biotin has previously been suggested to be essential in biotin's mechanism of action. In a series of investigations on structure-function relationships with biotin analogs not containing the sulfur atom, the biotin analogs, azabiotin, bisnorazabiotin, carbobiotin and isoazabiotin enhanced guanylate cyclase, an enzyme that has recently been demonstrated to be activated by biotin. These analogs increased guanylate cyclase activity two-fold in liver, cerebellum, heart, kidney and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Previous studies provide convincing evidence that biotin and its metabolite biotinyl-AMP activate soluble guanylate cyclase, increasing the synthesis of cGMP (22, 40, 41). Subsequently, cGMP activates PKG, thereby increasing the transcription of genes coding for biotin-dependent carboxylases and holocarboxylase synthetase (22).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies provide convincing evidence that biotin and its metabolite biotinyl-AMP activate soluble guanylate cyclase, increasing the synthesis of cGMP (22, 40, 41). Subsequently, cGMP activates PKG, thereby increasing the transcription of genes coding for biotin-dependent carboxylases and holocarboxylase synthetase (22).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the effects attributed to B complex vitamins can be reproduced by this intracellular messenger by itself. In a recent investigation using biotin analogues, only those with biological activity were able to enhance guanylate cyclase activity [13]. The analogues without biological activity did not enhance guanylate cyclase activity [13].…”
Section: Discussionmentioning
confidence: 99%
“…Without the guanylate cyclase cofactor manganese present, biotin is unable to maximally stimulate guanylate cyclase activity [13]. A series of experiments were done to determine whether the concentration of the guanylate cyclase cofactor manganese affected any of the B complex vitamins' activation of hepatic guanylate cyclase.…”
Section: Interrelationship Of the Guanylate Cyclase Cofactor Manganesmentioning
confidence: 99%
“…Previous studies have shown that pyridoxine including the other B complex vitamins promote their effects by activating GC via enhancing cGMP levels [17,28].…”
Section: Discussionmentioning
confidence: 99%